Inequality and Extremist Voting: Evidence from Germany - Florian Dorn; Clemens Fuest; Lea Immel; Florian Neumeier (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the impact of economic inequality on political polarization. Using a unique dataset covering different measures of regional income inequality as well as federal and state election outcomes at the county level in Germany, we investigate whether inequality influences the share of votes for right-wing and left-wing extremist parties using instrumental variable estimation. Our results suggest that an increase in income inequality has a sizeable influence on the support for extremist parties. The poorer a county is compared to the national average, the higher is the share of votes both nationalist and leftist parties receive. Our findings thus indicate that the rise in economic inequality may be a threat to political stability.
Keywords: C26; D31; D63; D72; R1; C26; D31; D63; D72; R1; 330; Inequality; political polarization; extremist voting; Germany